Krisis Identitas dan Konversi Agama dalam Perspektif Psikologi Agama: Studi Kasus pada Pelaku Married By Accident (MBA) - Rut Marchel Avellia; Yulius Yusak Ranimpi; Rama Tulus Pilakoannu (Airlangga University Press, Universitas Airlangga, 2023)
Identity in the individual refers to the individual's awareness of oneself (true self) concerning various social roles. Identity development occurs during adolescence. During this period, they will explore multiple roles in society to determine their identity, including religious identity. The existence of religious conversion will have an impact on the development of their identity. The purpose of this study is to describe the identity crisis caused by religious conversion. The participant in this study is a 21-year-old woman who had converted her religion at the age of 18 due to marriage. The method used is a case study. Data were collected by conducting interviews. This study shows that religious conversion carried out by participant is considered to be the only way to solve the problem. In that condition, the participant experienced identity confusion which later became self-isolation, such as breaking off relations with peers and avoiding her new communities.